2022
DOI: 10.3389/fenvs.2022.898934
|View full text |Cite
|
Sign up to set email alerts
|

Contamination characteristics, coexistence relationships and health risk assessment of dioxins and metals in topsoil around municipal solid waste incinerator in Hainan, China

Abstract: Highly toxic pollutants such as dioxins and metals emitted from municipal solid waste (MSW) incineration have caused a serious not-in-my-backyard social phenomenon. However, relatively few studies have comprehensively analyzed the contaminant characteristics, coexistence relationships and potential health risks of dioxins and metals in soils near MSW incinerator. Therefore, this study monitors 17 dioxin homologues and 13 metals in soils around MSW incinerator to evaluate their contaminant and coexistence chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…significantly lower than those of the studies on soils surrounding the operated MSW incineration plants in Sichuan [11], East region [15] and Shanghai [85] in China, Spain [61,86] and Korea [87], but higher than that of the research focusing on Hainan (i.e., a relatively polluted region) in China [88]. Overall, the baseline health risks (involving the CR and NCR) from dioxins in soils near the pre-construction MSW incineration plants of this study are relatively low and below the acceptable level, suggesting no significant adverse effects on human health.…”
Section: Comparative Analysis Of Health Risksmentioning
confidence: 62%
“…significantly lower than those of the studies on soils surrounding the operated MSW incineration plants in Sichuan [11], East region [15] and Shanghai [85] in China, Spain [61,86] and Korea [87], but higher than that of the research focusing on Hainan (i.e., a relatively polluted region) in China [88]. Overall, the baseline health risks (involving the CR and NCR) from dioxins in soils near the pre-construction MSW incineration plants of this study are relatively low and below the acceptable level, suggesting no significant adverse effects on human health.…”
Section: Comparative Analysis Of Health Risksmentioning
confidence: 62%
“…Many studies have been reported on risk assessment of heavy metal pollution in soil around MSW incineration plants [12][13][14][15][16][17][18]. However, it is still debated whether MSW incineration plants have a significant impact on the content of heavy metal elements in the surrounding soil.…”
Section: Introductionmentioning
confidence: 99%